1979
DOI: 10.1079/bjn19790088
|View full text |Cite
|
Sign up to set email alerts
|

Long-term vitamin status and dietary intake of healthy elderly subjects

Abstract: I . Long-term clinical and biochemical vitamin C (ascorbic acid and dehydroascorbic acid) status and dietary intake of vitamin C were monitored for 18 months in twenty-three relatively-healthy elderly subjects living at home in the north of England.2. Plasma vitamin C showed a strong positive correlation with buffy-coat vitamin C both cross-sectionally between subjects and longitudinally within subjects; plasma levels, therefore, were almost as good an index of Iong-term status as buffy-coat levels.3. Vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Furthermore, plasma vitamin C concentration has been shown to be highly correlated with buffy-coat (leukocyte) vitamin C concentration and was an equally good index of long-term status over 18 months [28]. In addition, in the same study, a single measure of vitamin C concentration ranked individuals as well as the mean of six measures taken over the 18-month period and plasma vitamin C concentration correlated well with the longterm intake of vitamin C in that study [28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, plasma vitamin C concentration has been shown to be highly correlated with buffy-coat (leukocyte) vitamin C concentration and was an equally good index of long-term status over 18 months [28]. In addition, in the same study, a single measure of vitamin C concentration ranked individuals as well as the mean of six measures taken over the 18-month period and plasma vitamin C concentration correlated well with the longterm intake of vitamin C in that study [28].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the National Diet and Nutrition Survey of people aged 65 years and over has added to the findings of earlier British surveys and studies of older people (Department of Social Security, 1972, 1979;Bates et al 1979Bates et al , 1980Rutishauser et al 1979;Department of Health, 1992). People aged 65 years or over living in mainland Britain had micronutrient intakes which were, with the possible exception of four nutrients, generally within the range considered adequate by comparison with the dietary reference values (Department of Health, 1991).…”
Section: Biochemical Status Indicesmentioning
confidence: 99%
“…It may be argued that the use o f a single measure to determine vitamin C status may be subject to misclassification error. However, it has been demonstrated that although higher dietary vitamin C intakes are associated with more intra-individual variation in serum levels than low intake levels, a single measure is a good indicator of chronically low levels of vitamin C intake (Jacob, Skala & Omaye, 1987;Bates, Rutishauser, Black et al, 1979).…”
Section: Discussionmentioning
confidence: 99%